First Report of Small Skeletal Fossils from the Upper Guojiaba Formation (Series 2, Cambrian), Southern Shaanxi, South China - Mei Luo; Fan Liu; Yue Liang; Luke C. Strotz; Jiayue Wang; Yazhou Hu; Baopeng Song; Lars E. Holmer; Zhifei Zhang (Biology, 2023)
A small skeletal fossil assemblage is described for the first time from the bioclastic limestone interbeds of the siltstone-dominated Guojiaba Formation, southern Shaanxi, China. The carbonate-hosted fossils include brachiopods (Eohadrotreta zhujiahensis, Eohadrotreta zhenbaensis, Spinobolus sp., Kuangshanotreta malungensis, Kyrshabaktella sp., Lingulellotreta yuanshanensis, Eoobolus incipiens, and Eoobolus sp.), sphenothallids (Sphenothallus sp.), archaeocyaths (Robustocyathus sp. and Yukonocyathus sp.), bradoriids (Kunmingella douvillei), chancelloriids sclerites (Onychia sp., Allonnia sp., Diminia sp., Archiasterella pentactina, and Chancelloria cf. eros), echinoderm plates, fragments of trilobites (Eoredlichia sp.), and hyolithelminths. The discovery of archaeocyaths in the Guojiaba Formation significantly extends their stratigraphic range in South China from the early Tsanglangpuian at least to the late Chiungchussuan. Thus, the Guojiaba Formation now represents the lowest known stratigraphic horizon where archaeocyath fossils have been found in the southern Shaanxi area. The overall assemblage is most comparable, in terms of composition, to Small skeletal fossil (SSF) assemblages from the early Cambrian Chengjiang fauna recovered from the Yu’anshan Formation in eastern Yunnan Province. The existing position that the Guojiaba Formation is correlated with Stage 3 in Cambrian Series 2 is strongly upheld based on the fossil assemblage recovered in this study.